The Role of Social Identity and Communities of Practice in Mergers and Acquisitions. Issue 4 (August 2018) - Spoor, Jennifer R.; Chu, Mei-Tai
Globally, organizations spend billions on mergers and acquisitions (M&As) each year; however, it is commonly estimated that at least half of these ventures fail. Two factors that contribute to this high failure rate are the difficulty in merging diverse areas of organizational knowledge and developing employees' organizational identification with the post-M&A organization. In this article, we recommend the strategic use of organizational communities of practice (CoPs), groups where people share knowledge, to improve knowledge sharing within the post-M&A organization. We also argue that CoPs can indirectly increase knowledge sharing by easing M&A-triggered social identity concerns and fostering post-M&A organizational identification. We develop conceptual propositions for the relationships between CoPs participation, organizational identification, and knowledge sharing in the post-M&A organization. We also argue that the extent to which CoPs participation can increase organizational identification and knowledge sharing will depend on the post-M&A organization's overall business strategy and whether it is primarily concerned with explicit or tacit knowledge.